Dynamic mode III interface crack in aluminum matrix composites. Issue 1 (1st June 2015) - Hao, Guodong; Xiang, Qian; Lü, Nianchun; Wang, Yuntao
Abstract : By means of the theory of complex variable functions, dynamic extension queries on symmetrical mode III interface crack in aluminum alloys and aluminum matrix composite materials were studied. The crack extension should also appear in the format of self-similarity because interface failure is ascertained by the maximum tensile stress. The formulation involves the development of a Riemann–Hilbert problem. The queries, considered in this study, can be very readily translated into Riemann–Hilbert problem by ways of self-similar functions. The general representations of analytical solutions of stresses, displacements and dynamic stress intensity factors, for the edges of symmetrical mode III interface crack, subjected to motive enhanced loadings, Px 5 /t 5 and Pt 6 /x 5, respectively, were obtained. In light of the correlative material properties, the changeable law of dynamic stress intensity factor was illustrated very well. After the solutions were utilized by the use of superposition principle, the solutions of discretionally complicated problems were easily acquired.